Multi-expert multi-criteria decision support model for traffic control - Gramajo, Sergio D. (2012)
The common use of IP networking structures implies the increasing demand of resources by users and applications. For this reason, organizations must guarantee adequate conditions for critical traffic. To face this problem, network administrators constantly need to make decisions regarding this situation by means of using different strategies and tools of Quality of Service (QoS), such as Traffic Control (TC). Such decisions can be modeled by a decision support system that handles subjective information about decision maker’s perceptions. This information involves uncertainty and requires precise evaluation of traffic quality demanded. Subjectivity is modeled by using linguistic information (LI) in order to choose adequate solution to networking performance problems. This paper proposes a Multi-Expert (ME) Multi-Criteria (MC) Linguistic Decision Making (LDM) Model for TC in networking. Finally, an application example to show the model’s benefits is presented.